ANALISIS INTERNAL CONTROL AKUNTANSI PENJUALAN PADA PT. POMAL TANI MANDIRI BANDAR LAMPUNG - Fransiska Wahyu Lestari; Desma Susanti (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2016)
Sales accounting information system is needed to provide evidence of adequate recordingand reporting on all activities of the company's sales, so it can be useful information for the benefit ofthe leadership in decision-making ( Mulyati, 2005). Internal control system by Mulyadi (2008 : 163 )includes organizational structure, methods, and coordinated measures which aim to keep the wealthof the organization, check the accuracy and reliability of accounting data, promote efficiency andencourage compliance managementHowever, in the company there are some system cash sales and credit sales are not inaccordance with the theory. For cash sales system that is not in accordance with the theory that thesales department , the warehouse / delivery of goods, and parts shipments. As for credit sales, partof which is not in accordance with the theory that the sales department, the warehouse / delivery ofgoods, parts delivery, billing section .